Does Power Sector Reform Facilitate Informal Economy Development? A Study of Nigeria’s Experience in the Southeast Geopolitical Zone - Chukwu, Chukwuemeka Quentin; Ojohu, Richard; Nnamani, Kelechi Elijah (Unisia, 2022)
This study examines the efficacy of the power sector reform in enhancing the development of the informal economy in the southeast geopolitical zone of Nigeria. It interrogates explicitly the effect of the unbundling of the electricity sector on job creation and livelihoods of the operators of the informal economy. Utilizing the mixed methods data approach and the Marxist theory of the postcolonial state, this study argues that the power sector reform is part of the grand strategy aimed at expanding capitalist penetration and protecting the economic interests of the advanced capitalist states. This self-serving interest of the capitalist institutions, which the power sector reform intends to protect explains the crisis in the power sector manifesting in poor electricity supply and increased tariffs for electricity consumers. Indeed, these untoward outcomes have negatively affected the development of the informal economy in southeast Nigeria. It, however, recommends a reevaluation of the market-based power sector reform in Nigeria.